Validation of methodology for recording breathing and simulating drug delivery through spacers and valved holding chambers - Schultz, A.; Le Souëf, T.; Looi, K.; Zhang, Guicheng; Le Souëf, P.; Devadason, S. (Mary Ann Liebert, Inc. Publishers, 2010)
Background: Output from spacers (or valved holding chambers) is sensitive to changes in breathing pattern. Different spacers have unique characteristics that may influence breathing. A method used for breathing simulation, where the simulated breathing can be recorded on subjects while they are using spacers, may allow for more accurate in vitro estimation of drug delivery in specific populations, using specific spacers. Methods: A flow chamber was used to record breathing while salbutamol was administered to two adult subjects through different spacers. Each subject performed a series of breathing patterns over a range of different inhalation volumes and flows. Salbutamol "inhaled" by subjects was captured on inspiratory filters and quantified by ultraviolet spectrophotometry. Recorded breathing patterns were simulated and ex vivo drug delivery was compared to in vitro drug delivery. Three equipment configurations were used to validate different aspects of the methodology. Configuration 1: breathing recorded by pneumotachometer placed directly between a human subject and the spacer. Breathing simulation performed with an identical setup. Configuration 2: spacer enclosed within a flow-chamber while breathing was recorded. Breathing simulation performed with an identical setup. Configuration 3: spacer enclosed in flow chamber to record breathing, but not when simulating breathing. In each configuration, the ex vivo and in vitro (simulated) filter doses were compared. Results: Configuration 1: the median difference between ex vivo and in vitro filter doses was 0.4% (range: -12.2 to 6.9%). Configuration 2: the median difference was -2.3% (range: -9.0 to 5.0%). Configuration 3: the median difference was 1.7% (range: -11.5 to 3.9%). Conclusion: Our results indicate that in vitro simulated drug delivery using this method of recording using a flow chamber, closely approximates ex vivo total drug delivery. This technique allows for recording of breathing on patients while they are using spacers, with minimum increase in dead space or resistance, and no physical alteration in the patient-device interface. © Copyright 2010, Mary Ann Liebert, Inc. 2010.